LEXICAL METAPHOR IN SURA' AL WAQI'AH - M. Arief Rahman; Tanjung, Ahmad Khoirul Akhir; Zidni Ma'ruf (International Journal of English Language and Pedagogy, 2023)
This study deals with lexical metaphor in Sura’ Al Waqi’ah by applying Systemic Functional Linguistics (SFL). The objectives of the study are to describe the types of lexical metaphor used in Sura’ Al Waqi’ah, how are the metaphors used in Sura’ Al Waqi’ah, and the reason for the use of lexical metaphor in Sura’ Al Waqi’ah. This study was conducted by using descriptive research. The sources of data were Sura’ Al Waqi’ah. The findings indicated that firstly, there are three concepts of lexical metaphor in Sura’ Al Waqi’ah such as 13 verses (23.21%) for noun–noun concept, 23 verses (41.07%) for noun-verb concept or verb-noun concept and 20 verses (35.71%) for noun- adjective concept or adjective-noun concept. Secondly, linguistics realization of Lexical Metaphor in Sura’ Al Waqi’ah are through comparing noun–noun, noun-verb or verb-noun and noun–adjective or adjective-noun. Finally, the reasons of lexical metaphors used in Sura’ Al Waqi’ah are explaining the idea which is out of human life experience, explaining an abstract thing concretely and explaining something unknown yet with something familiar. Sura’ Al Waqi’ah tells us about the resurrection day. This Sura’ explains about what will happen before and after resurrection day. Resurrection day is an abstract thing. No one in this world has experience about the resurrection day. So, this Sura’ mostly discusses about it. That’s why, the most dominant reason of using lexical metaphor in Sura’ Al Waqi’ah is explaining an abstract thing concretely.